Pathogen resistant genetically engineered crops in Africa - Tripathi, L.; Kumar, P. Lava; Patil, B.L.; Fatokun, C.A. (Studium Press LLC, 2015)
Diseases caused by viral, fungal and bacterial pathogens pose great threat to food security in Africa. Use of disease resistant cultivars is among the most preferred tactic for disease control by smallholder farmers in Africa, who cannot afford cost intensive chemical inputs or labor intensive crop management practices. A number of disease resistant staple crop cultivars have been developed through transfer of resistance genes from cultivars and other cross compatible relatives through conventional breeding approaches. Genetic enhancement through transgenic technology is also being used to develop disease resistant cultivars in situations where conventional breeding is difficult or disease resistance is unavailable in the crop’s gene pool.Many of the on-going initiatives ondisease resistant genetically engineered (GE) crops in Africa have been targeting pathogens of high economic importance (e.g., banana bacterial wilt, cassava brown streak, cassava mosaic, and maize streak) affecting smallholder farmers; they are publicly funded and GE technology is offering promising solution against some of the most important diseasesthat include banana bacterial wilt, cassava brown streak, sweet potato virus complex and others. Disease resistant GE crops are yet to be released for farmer cultivation, but confined field trials are in progress in a number of countries. The status and prospects of pathogen resistant GE crops in Africa, with a special emphasis on banana with resistance to xanthomonas bacterial wilt and cassava resistant to cassava mosaic and cassava brown streak virus diseases are summarized in this chapter.